Heat Generation and Chemical Reaction Effects On MHD Flow Over An Infinite Vertical Oscillating Porous Plate With Thermal Radiation (International Journal of Engineering and Computer Science, 2014)
The work is focused on the non linear MHD flow   heat and mass transfer characteristics of an incompressible, viscous, electrically conducting and Boussinesq fluid over a vertical oscillating porous permeable plate in presence of homogeneous chemical reaction of first order, thermal radiation  and heat generation effects. The problem is solved analytically using the perturbation technique for the velocity, the temperature, and the concentration field. The expression for the skin friction, Nusselt number and Sherwood number are obtained. The effects of various thermo-physical parameters on the velocity, temperature and concentration as well as the skin-friction coefficient, Nusselt number and Sherwood number has been computed numerically and discussed qualitatively.